Improved the growth and yield of rubber at mature period throught Iles-Iles (Amorphophallus muelleri Blume) intercropping - Sahuri Sahuri (Universitas Trunojoyo Madura, 2023)
Rubber plants that have produced can be improved through iles-iles farming. This study aims to determine the effect of the iles-iles rubber intercropping system on soil fertility, rubber growth, and latex yield. The study used a completely randomized block design (CRBD) with three replications. The treatment compared the rubber monoculture system with iles-iles rubber intercropping. The results showed that the cultivation of iles-iles as a rubber intercropping during the mature period of two years of observation did not inhibit the growth of rubber because it was not significantly different (P = 0.255) compared to the monoculture system but had a significant (P = 0.0013) effect on the latex yield. The BEP (Break Event Point) value of this farming system was achieved at the price of wet tubers of IDR 7.139 kg-1 with a production of 2.368 kg ha-1, while the value of the LER (Land Equivalent Ratio) in this farming system was 1.84.